Efeito de diferentes sais de ferro sobre as características sensoriais do iogurte de soja - Cardoso Umbelino, Daniela [UNESP]; Bolini Cardello, Helena Maria André [UNESP]; Rossi, Elizeu Antonio [UNESP] (My University, 2001)
The soy-yogurt was used as food vehicle due to its therapeutic and nutritionalproperties and lower cost. The aim of this work was to develop an enriched soy-yogurt with 12 mg of elementary iron/1, with suitable sensory and technological properties. Four iron sources were tested: FeSO 4.7H 2O, NaFeEDTA, Ferrochel® and microencapsulated FeSO 4.7H 2O. The products were evaluated by fermentation time, pH, titratable acidity, viscosity, consistency, iron concentration and sensory properties (difference from the control and acceptance tests). Viscosity and consistency data were submitted to analysis of variance and Tukey's test. Difference from the control data was evaluated by analysis of variance and Dunnett's test and the acceptance test was evaluated by analysis of variance and Tukey's test. For all iron salts used in the enrichment process, only the FeSO 4JH 2O did not work out because of the undesirable sensorial characteristics of the final products. The others sources used in the enrichment process (NaFeEDTA, Ferrochel® and microencapsulated FeSO 4.7H 2O) did not alter the fermentation time, titratable acidity and sensory and reologics properties of the soy-yogurt.
Keywords: Calcium; Enrichment; Iron; Sensory analysis; Soy-yogurt